Spatial and temporal dynamics of whalewatching in Península Valdés, Patagonia, Argentina - Fazio, Ana; Arguelles, Maria Belen; Bertellotti, Marcelo (J. Cetacean Res. Manage., 2023)
Península Valdés (Patagonia, Argentina) is considered one of the best places in the world to watch southern right whales (Eubalaena australis) due to the large number of animals as well as to their predictability and proximity to the coast. The present study describes the spatial and temporal dynamics of whalewatching, and the different groups of whales that were the focus of this activity in Península Valdés during six reproductive seasons (from 2005 to 2008 and from 2012 to 2013). The aim was to generate useful tools to improve whalewatching activity in this area. Data were recorded from 1,816 whalewatching trips operated from Puerto Pirámides. Every trip had several stopovers to watch whales, defined as ‘sightings’. At the beginning of the season, most sightings occurred near Puerto Pirámides port, while at the end of the season, sightings were farther from the port. During the first half of the whale season, trips tended to be coastal and shorter but the groups of whales sighted were more varied, including solitary animals, mating groups and mothers with their recently born calves. In the second half of the season, trips tended to be further from the coast and longer, but the whales sighted were mainly mother-calf pairs, the last group of whales to leave the area. This difference in the characteristics of the sightings as the whale season progressed could be the basis to generate different recreational experience opportunities. Whalewatching has a major impact on the regional economy and whalewatching regulations, if correctly applied, could improve the quality of a conservation plan, considering that both gulfs of Península Valdés (San José and Nuevo) are the main calving areas for this species in the South Atlantic Ocean.